Elderly Patients with Atrial Fibrillation: Focus on Comorbidity and Safety of Anticoagulant Therapy - D. A. Napalkov; A. A. Sokolova (Рациональная фармакотерапия в кардиологии)
The article discusses issues related to the prescription of anticoagulant therapy to elderly patients with atrial fibrillation (AF), especially those over 70 and 80 years of age. The relevance of the issue is primarily due to the prevalence of AF in this cohort of patients, and the second is due to the higher incidence of comorbidity. The presented material demonstrates the peculiarities of anticoagulant therapy application in groups of patients older than 75, based on the data of randomized clinical trials, and also presents extrapolation of the results of RCTs to the real clinical practice (data of registers and cohort trials). The use of unreasonably low doses of oral anticoagulants in elderly patients is debated. It often leads to a decrease in the efficacy of anticoagulant therapy without improving the drugs safety profile. A new validated scale (ABH) for evaluating of anticoagulant therapy safety is presented in the article. The ABH scale can be used before prescribing to patients exactly direct oral anticoagulants. This scale is simpler and more practical than the HAS-BLED scale. The data for the ABH scale are validated based on direct oral anticoagulants in 21,248 patients from the Norwegian register. The presented results demonstrate a favorable efficiency and safety profile of rivaroxaban in comparison with warfarin in patients 75 years and older. Thus, the overall benefit for the use of rivaroxaban against warfarin in patients > 75 years of age in the subanalysis of the ROCKET-AF study was statistically significantly greater than in younger patients with AF. Data on 11121 patients with AF who were treated with rivaroxaban for the prevention of stroke and systemic embolism are included in the combined analysis of the XANTUS, XANAP and XANTUS-EL registers. 96% of patients in the study did not have serious thromboembolic events. The amount of major bleeding was 1.7 per 100 patient-years, and gastrointestinal bleeding was 0.7 per 100 patient-years. This turned out to be less than in some other registry studies. In addition, patients showed good adherence to rivaroxaban treatment: after a year, 77.4% of patients continued to take the drug.